ROLE OF AGNI KARMA IN SNAYU VIKARA W.S.R. TO TENNIS ELBOW (International Journal of Ayurveda and Pharma Research, 2015)
The Tennis Elbow is likely to be the most common insertional tendinopathy of the human body and is found to be associated with some particular occupations and life style. No such disease has been mentioned in the Ayurvedic text. Here in the OPD of R.G.G.P.G.A.C. & Hospital, we have a very good no. of patients of Tennis Elbow, who dont get relief by the conservative management and also do not want to go for Local anesthetic and hydrocortisone. And also it is found that Local anesthetic and hydrocortisone is not a standard treatment for these patients and the surgery is beyond the capacity of the patients of a developing country like ours and also has its own risk. In Sushruta samhita, Agnikarma has been mentioned for disorders of Snayu (ligaments and tendons), Asthi (bone), Sandhi (joints). In Ayurveda, Snayu Vikara can be correlated with the condition of tennis elbow. This therapy provided considerable relief in pain and movement of the elbow joint. Therefore, a study has been designed to understand this disease on Ayurvedic principles and to establish a standard treatment, which can cure this disease or provide long term relief and within the reach of common man and without any side effect.